Medida da evaporação no solo com uso de microlisímetro de pesagem sob condições de Caatinga preservada - Epondina, Aloys Edilon (2023)
The evaporation of water from the soil in the Caatinga can be quantified by several methods, the most used are meteorological, energy balance, sap flow, and the lysimetry technique. Microlysimeters (ML) consist of tanks that delimit a small volume of soil and allow measuring the water balance in that soil with greater precision. It is noteworthy that data obtained with this method in forests are extremely rare throughout the southern hemisphere of the planet, especially in semi-arid regions. Therefore, the objective of this work was to measure the evaporation of water from the soil in preserved Caatinga conditions during the rainy season and the dry season. For this, measurements were carried out in the field, in the Aiuaba Experimental Basin (BEA), a semi-arid region with a high level of preservation, from July 2021 to August 2022. Two undisturbed samples of chromic Luvissol were used and overlapped on the platforms of weighing connected to data storage systems (dataloggers). The equipment used in the research corresponds to two cylindrical microlysimeters measuring 0.20 m in diameter and 0.40 m deep. The MLs were installed in the field, in the sub-canopy of the Caatinga vegetation preserved in BEA. A 0.15 m layer of pebbles was placed in the pits (0.80 m deep) to promote drainage. The height of the weighing platform corresponds to 0.25 m. External PVC tubes were introduced to protect the soil sample and the undisturbed soil samples were inserted in the central part of the external tubes. To monitor the moisture content of this soil sample, two TDR soil moisture sensors were installed at a depth of 0.20 m and another at 0.40 m. The rate of soil water depletion under preserved Caatinga conditions was recorded throughout the period. The results indicate that the highest value of water evaporation in the soil corresponds to 3.9 mm/day, observed in the month of May 2022 and the lowest evaporation rates occurred in June 2021, with values around 0.70 mm/day. 70% of the time the evaporation of water in the soil presents values very close to zero. The soil evaporation coefficient under study revealed that during the dry period, soil evaporation represents only 0.70% of the reference evaporation. During the rainy season, it represents an average of 76% of the reference evaporation and can reach 130% of the reference evaporation. Being 30% higher. The low-cost microlysimeter technique in semi-arid forests is promising.